Development of E-Worksheet Assisted by Liveworksheets to Improve Science Process Skills and Collaboration on Chemical Equilibrium Materials - Alifia Felitasari; Rusmini Rusmini (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This study aimed to determine the feasibility of e-worksheet assisted by liveworksheets to improve science process skills and collaboration on chemical equilibrium materials based on aspects of validity, practicality, and effectivity. This type of research is research and development using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The participants of the limited trial were 30 students of class XI Science at ITP Senior High School in Surabaya. The method used is interviews, questionnaires, observations, and tests. This study uses an analysis technique that combines qualitative elements and quantitative elements. Qualitative elements were analyzed descriptively. Quantitative elements were analyzed using Aiken's V analysis, percentage analysis, normality test (Shapiro-Wilk Test), Paired Sample T-Test, and N-Gain analysis. The results of the validity with a value of 0.81 which is categorized as very valid. The practical results with the percentage value of the questionnaire responses and observations of students are 88% and 80.66% in the very good category. The effectivity results in the value of N-Gain cognitive and science process skills of 0.67 and 0.68 with the medium category. And the results of the questionnaire and observation of collaboration skills are 94% and 89% in the very good category. So, it can be concluded that e-worksheet assisted by liveworksheets can improve students' science process skills and collaboration on chemical equilibrium.